The Day After Peace - Gilley, Jeremy (Peace One Day Production, 2008)
Verzio FF Submission “The Day After Peace” charts the remarkable 10-year journey of award-winning filmmaker Jeremy Gilley to establish an annual Peace Day on 21 September. The camera follows Jeremy as he galvanizes the countries of the world to recognize an official day of ceasefire and non-violence. But even after the member states of the UN unanimously adopt Peace Day, the struggle is not over. As the years pass, there is not a single ceasefire. The voices of the cynics are growing louder – and now Gilley’s non-profit organization, Peace One Day, is in dire financial straits. But he can not let it fail.